Ubiquitin ligase SMURF1 functions as a prognostic marker and promotes growth and metastasis of clear cell renal cell carcinoma. Issue 4 (23rd February 2017) - Ke, Mang; Mo, Licai; Li, Weilin; Zhang, Xianjun; Li, Feiping; Yu, Hongyuan
Abstract : Smad ubiquitin regulatory factor 1 (SMURF1), a recently identified E3 ubiquitin ligase, targets substrate proteins for ubiquitination and proteasomal degradation. Previous studies have reported that SMURF1 also functions as an oncogene in human cancers. However, the clinical value of SMURF1 and its role in clear cell renal cell carcinoma (ccRCC) are unknown. SMURF1 expression was analyzed in 100 cases of ccRCC and matched tumor‐adjacent specimens. SMURF1 was prominently overexpressed in ccRCC specimens compared with tumor‐adjacent specimens. Increased levels of SMURF1 were also observed in ccRCC cell lines. Clinicopathological detection verified that SMURF1 expression was associated with advanced tumor node metastasis stage, large tumor size and vascular invasion of ccRCC patients. Moreover, Kaplan–Meier analysis found that SMURF1 elevation led to adverse overall survival and disease‐free survival. Multivariate Cox regression analysis revealed that SMURF1 expression was an independent marker for prognosis prediction. Further experiments illustrated that SMURF1 knockdown significantly inhibited growth and metastasis of 769P cells, while SMURF1 overexpression promoted proliferation, migration and invasion in OSRC‐2 cells. Mechanistically, SMURF1 inversely regulated the expression of DAB2 interacting protein, which negatively mediated the activation of both the ERK/RSK1 and PI3K/AKT/mTOR pathways in ccRCC cells. Taken together, these results suggest that SMURF1 might be a promising biomarker and target for novel treatment of human ccRCC. Abstract : SMURF1 is involved in the development and progression of various cancers, but its role in clear cell renal cell carcinoma (ccRCC) was uncertain. We found that SMURF1 was overexpressed in ccRCC tissues and cells, and that this was associated with poor clinical parameters and prognosis for ccRCC patients. SMURF1 promotes growth and metastasis of ccRCC cells, with DAB2 interacting protein a direct target.